Social Capital Inequalities among Postgraduate Students and Social Selection Processes - Crepalde, Neylson J. B. F. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM); 2017: Anais do VI Brazilian Workshop on Social Network Analysis and Mining, 2017)
This paper aims to discuss social capital inequalities between postgraduate students enrolled in a social sciences program in a Brazilian university. I analyze data from 47 postgraduate students using linear models, stochastic blockmodelling and the Social Selection Model (SSM). The analysis shows that social formations occur mainly from participation in research groups and from methodological perceived habilities.